2020
DOI: 10.1002/biot.202000177
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the Manufacture of Human CAR‐T Cells in an Automated Stirred‐Tank Bioreactor

Abstract: Chimeric antigen receptor T‐cell (CAR‐T) therapies have proven clinical efficacy for the treatment of hematological malignancies. However, CAR‐T cell therapies are prohibitively expensive to manufacture. The authors demonstrate the manufacture of human CAR‐T cells from multiple donors in an automated stirred‐tank bioreactor. The authors successfully produced functional human CAR‐T cells from multiple donors under dynamic conditions in a stirred‐tank bioreactor, resulting in overall cell yields which were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…However, the present approaches impact on consistency of production and cell quality as well as being very expensive and the establishment of scalable, controlled stirred systems should lead to a much better and cheaper process. The work summarized here is a significant move towards that goal [33,49].…”
Section: Free Suspension Culturementioning
confidence: 95%
See 4 more Smart Citations
“…However, the present approaches impact on consistency of production and cell quality as well as being very expensive and the establishment of scalable, controlled stirred systems should lead to a much better and cheaper process. The work summarized here is a significant move towards that goal [33,49].…”
Section: Free Suspension Culturementioning
confidence: 95%
“…This finding reinforced the concept that once agitation was intense enough to ensure adequate suspension of the activating Dynabeads®, the cells were able to effectively proliferate, with, in each case, the CAR‐T cells retaining the expression of the CAR gene and their efficacy to target and kill leukaemia cells in vitro. Overall, the two studies 33, 49 showed that fluid dynamic stresses in stirred bioreactors did not damage these cells but that they gave an improved performance compared to static T‐flasks even though λ K at the highest specific power used was of the order of the size of the cell 33.…”
Section: Impact Of the Scale Of The Organismmentioning
confidence: 96%
See 3 more Smart Citations